Entrepreneurial attitude in female Latin American university students: internal and external influences - Víquez-Paniagua, Ana Gabriela; Leiva-Bonilla, Juan Carlos; Mora-Esquivel, Ronald (Instituto Tecnológico de Costa Rica, 2022)
Purpose – The aim of this study is to examine the influence of locus of control, the university environment, and the social environment on the entrepreneurial attitude of female Latin American university students. Design/methodology/approach – The study applies a Quan-qual design. The Quan section analyses the data of 10,781 female university students from eleven Latin American countries included in the GUESSS Survey, 2018. A hierarchical multiple regression analysis was applied. The qual section applies in-depth interviews for sequential methodological triangulation analysis. Findings – The evidence indicates that locus of control, the university environment, and the social environment positively impact the entrepreneurial attitude of female Latin American university students. The most influential factor was locus of control. Originality/value – This empirical study focuses on female university students and their propensity for business venturing and determines the main influences on their entrepreneurial attitudes.

Objetivo – Este estudio tiene como objetivo examinar la influencia del locus de control, el entorno universitario y el entorno social en la actitud emprendedora de las estudiantes universitarias latinoamericanas. Diseño/metodología/enfoque – El estudio aplica un diseño Quan-qual. La sección Quan analiza los datos de 10.781 estudiantes universitarias latinoamericanas de once países, incluidas en la Encuesta GUESSS, 2018. Se aplicó un análisis de regresión jerárquica múltiple. La sección cualitativa aplica entrevistas en profundidad para un análisis de triangulación metodológica secuencial. Resultados – La evidencia indica que el locus de control, el entorno universitario y el entorno social impactan positivamente en la actitud emprendedora de las estudiantes universitarias latinoamericanas. El factor más influyente fue el locus de control. Originalidad/valor – Este estudio empírico se centra en las estudiantes universitarias y su propensión a emprender y determina las principales influencias de su actitud emprendedora.
Artículo. Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2022
Keywords: Actitud -- Mujeres; Emprendedores; Mujeres -- Universidad; Actitud -- Emprendimiento; Estudiantes universitarios; GUESSS; Negocios; Attitude -- Women; Entrepreneurs; Women -- University; Attitude -- Entrepreneurship; University students; Businesses; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::SOCIAL SCIENCES::Business and economics